Development of a Radio Frequency Remote-Controlled Amphibious Solid Waste Collecting Mobot - Jay Robert B. Del Rosario; Romwell B. Andutan; Adelfos R. Bautista; Patrick Henry L. Pangilinan; Ruby Anne O. Vega (Institute of Advanced Engineering and Science, 2016)
Robots in general are used to aid people in different tasks from simple activities to activities that prevent also people from harm. In fields of Robotics it is important that these robots are not complete replacements of humanity but mere tools that will improve human lives and more so save lives if possible. In this paper, the group presented a remote-controlled mobot with amphibious capabilities. The system is accessible through a radio frequency transmitter and receiver which there is an executable file that allows the mobot to be controlled. The characterization of the system and its performance are presented here as well.